Analysis Management of Tingkir Lor Tourism Village in Salatiga City - Nur Chasanah; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Analysis of Management of Tingkir Lor Tourism Village in Salatiga City is an effort to improve the welfare of the village community with all its potential. Tingkir Lor Tourism Village is a tourist village in Salatiga which has been inaugurated since 2015. The purpose of this study is to analyze the management process and find out the driving factors and inhibiting factors of the management of Salatiga Tingkir Lor Tourism Village. This study uses qualitative methods with data collection techniques of observation, interviews, and documentation. The results of the study indicate that the management process of Tingkir Lor Tourism Village has not gone well because there are still problems in planning, namely the unclear budget plan. Organizing, namely the division and grouping of work is still not appropriate, the distribution of authority has not gone well because the Decree on Organizational Management is unclear and lack of coordination. Actuating, namely lack of participation in the implementation of training activities provided by DISBUDPAR. Controlling, that is, the absence of the supervisory standards set. Supporting factors: the potential of the rice fields that are used as outbound activities, the whereabouts of Kyai Abdul Wahid's tomb. Inhibiting factors: low community participation, lack of cooperation, low quality of human resources, lack of commitment from the government.